Factors associated with self-perceived health status in Portugal: Results from the National Health Survey 2014 - Shaaban, Ahmed Nabil; Martins, Maria Rosario O.; Peleteiro, Bárbara (Frontiers in Public Health, 2022)
Background: Self-perceived health is an important indicator of illness and mortality. This study aims at identifying a wide range of factors that can influence self-perceived health status among a representative sample in Portugal. Methods: We used the 2014 National Health Survey (n=17057), whereby participants were required to assess their health status from “Very good”, “Good”, “Fair”, “Poor” to “Very poor”. We grouped the answers “Very good” and “Good”, and “Poor” and “Very poor”, respectively. Multinomial logistic regression was used to compare participants’ characteristics across groups by computing odds ratio and corresponding 95% confidence intervals. Models included Socioeconomic/demographic characteristics, objective health status, healthcare use, functional disability, barriers to healthcare services utilization, lifestyle variables, mental health status, social support, and satisfaction with life as potential factors that can affect self-perceived health. Models were adjusted for sex, age, educational level, degree of urbanization, and presence of chronic diseases. Results: About 45% of participants reported good/very good, 39% reported fair, while approximately 16% reported poor/very poor health perception. Poor/very poor health was more reported by women when compared to men (19.1% VS. 11.4%, respectively, p<0.001). A higher prevalence of poor/very poor health status was reported by participants living in thinly populated areas or among older populations. Lower educational levels, income, as well as unemployment, were found to increase the risk of reporting poor/very poor health status. Utilizing healthcare services more frequently, experiencing barriers to access healthcare services, having depressive symptoms or activity limitations, or lacking social support were found to be significantly associated with poor/very poor self-perceived health. Conclusion: Subjects living in Portugal tend to report less good/very good health status and more poor/very poor health when compared to the rest of Europe. This study stresses the importance of socioeconomic factors, chronic illness, barriers to access healthcare services, social isolation, and mental health status in influencing self-perceived health and highlights the urgent need for social-informed policies, strategies, and interventions to reduce health inequalities in Portugal.